If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10y + 10) + -1(3y + -1) = 0 Reorder the terms: (10 + 10y) + -1(3y + -1) = 0 Remove parenthesis around (10 + 10y) 10 + 10y + -1(3y + -1) = 0 Reorder the terms: 10 + 10y + -1(-1 + 3y) = 0 10 + 10y + (-1 * -1 + 3y * -1) = 0 10 + 10y + (1 + -3y) = 0 Reorder the terms: 10 + 1 + 10y + -3y = 0 Combine like terms: 10 + 1 = 11 11 + 10y + -3y = 0 Combine like terms: 10y + -3y = 7y 11 + 7y = 0 Solving 11 + 7y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 7y = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 7y = 0 + -11 7y = 0 + -11 Combine like terms: 0 + -11 = -11 7y = -11 Divide each side by '7'. y = -1.571428571 Simplifying y = -1.571428571
| 7x-5=2+6x | | -10-9= | | x+13=-12 | | 15x-(5x-8)=78 | | 18-7x=-52 | | 9x-(2x-7)= | | 3x+19y=-11 | | -2x=5x | | -2x=x | | 13p+4(4-8p)=-19+16 | | 8m+4m=36 | | 9x(6+8)=9x-26 | | 6A+10B+3B= | | 24=-2a | | 5x+8+10x+12=180 | | -5a+b=38 | | -4-5f+1=13 | | 10x+5=15x-10 | | x+2=4x-7 | | 5a+6b=18 | | -1-2x-7=18 | | 0.8(x+5)=5.2 | | 2x+3(x-2)-1=6x-(x+7) | | 4y^2=-5y+6 | | 4x+2+5x+10=90 | | 5+4x=2x+9 | | 20x+(5x+3)=103 | | -8(2x+8)+6= | | -x+4x-5=-32 | | x+2+3x-1=15 | | 789.23=0.25*q | | 9[19-4(8-5)]= |